Technology-Based Learning Management in Islamic Schools (Journal of Social And Education Research, 2025)
The development of information technology has transformed the dynamics of education, including in Islamic schools, making the implementation of technology-based learning management essential to improving the quality and effectiveness of the teaching and learning process. This study employs a literature review method by analyzing eight scholarly articles published between 2012 and 2025, aiming to identify best practices, implementation strategies, challenges, and the impact of technology on learning management. The analysis was conducted through content analysis and presented in a literature review table covering research focus and key findings. The results reveal that the successful implementation of technology largely depends on school leadership, teacher readiness and competence, facility support, curriculum management, and learning evaluation. Systematic managerial strategies enable optimal utilization of technology to enhance students’ motivation, engagement, and creativity while maintaining alignment with Islamic educational values. This study provides both theoretical and practical contributions to the development of Islamic education in the digital era and serves as a foundation for future research on the integration of technology in learning management.